Characterization physico-mechanical and chemical properties of nano-hydroxyapatite-silica added glass ionomer cement - Moheet, Imran Alam (2020)
The aim of this study was to synthesize and characterize different nanohydroxyapatite- silica (nano-HA-SiO2) particles with various silica concentrations and to investigate the effects of adding nano-HA-SiO2 to the conventional glass ionomer cement (Fuji IX GC). Nano-HA-SiO2 was synthesized using one-pot sol-gel technique, which was then characterized using fourier transform infrared spectroscopy (FTIR), x-ray diffraction (XRD), scanning electron microscope (SEM) and transmission electron microscope (TEM). Further investigations were carried out on nano-HA-SiO2 added glass ionomer cement (nano-HA-SiO2-GIC) to compare their mechanical (surface hardness, compressive strength, flexural strength, and shear bond strength), chemical (fluoride ion release, solubility and ion-exchange) and physical properties (colour stability, surface roughness, sorption and micro-leakage) in relation to conventional glass ionomer cement (cGIC). It was found that nano-powder consisted of a mixture of spherical silica particles (~50 nm) and elongated hydroxyapatite particles in the range between 100-200 nm. Hardness, compressive strength, and flexural strength of nano-HA-35SiO2-GIC was statistically higher than that of nano-HA–21SiO2–GIC, nano-HA-11SiO2-GIC. The highest value for Vickers hardness (64.77  6.18), compressive strength (143.42  13.94 MPa) and flexural strength (17.68  1.81 MPa) were recorded by addition of 10% nano-HA-35SiO2 to GIC, leading to an increase of ∼36 %, ∼19.7 % and ∼53.34 % in surface hardness, compressive strength and flexural strength respectively as compared to conventional glass ionomer cement (cGIC). 10% nano-HA–35SiO2-GIC also demonstrated higher shear bond strength (∼17.54 % increase) as compared to cGIC. Nano-HA-35SiO2-GIC was more colour stable material as it showed “slight - noticeable” change in colour as compared to cGIC that displayed “noticeable to appreciable” change after 28 days of immersion in distilled water. Nano-HA-35SiO2-GIC showed significantly lower surface roughness (0.13 ± 0.01 μm) as compared to cGIC (0.16 ± 0.03 μm) on day 1. Additionally, nano-HA-35SiO2-GIC showed highly significant difference (p=0.002) in amount of mean F+ release for all the time intervals as compared to cGIC (p ≤ 0.05). In addition, Nano-HA-35SiO2-GIC recorded higher values for both solubility and sorption (83.7 ± 19.04 μgmm-3 and 50.92 ± 12 μgmm-3) as compared to cGIC (56.65 ± 10.15 μgmm-3 and 42.64 ± 6.74 μgmm-3). It also exhibited lower micro-leakage both at occlusal and gingival margins (0.2 ± 0.42 and 2.7 ± 0.67) as compared to cGIC (0.5 ± 0.71 and 3 ± 0.00). A greater ion-exchange was displayed by nano-HA-35SiO2-GIC at ion-exchange layer (IEL) as well as the tooth structure (enamel and dentin) as compared to cGIC. The addition of nano-HA-silica to conventional GIC significantly enhanced the mechanical, physical and chemical properties except sol-sorption properties of the material. Based on the findings of the current study, nano-HA-SiO2-GIC can be suggested as a potential dental restorative material.